The value of therapeutic planning and the degree of experience of the surgical team on the results of cancer treatment of the larynx and hypopharynx - Carvalho, Marcos Brasilino de; Rapoport, Abrão; Fava, Antônio Sérgio; Góis Filho, José Francisco de; Chagas, José Francisco Salles; Kanda, Jossi Ledo; Sobrinho, Josias de Andrade; Kowalski, Luiz Paulo (São Paulo Medical Journal, 1995)
This is a prospective study supported by 170 cases of epidermoid carcinoma of the larynx or hypopharynx, treated during the period from January of 1981 to January of 1988, at the Head and Neck Surgery Service of the Heliópolis Hospital Complex, São Paulo. The objective of this project was to evaluate the importance of surgeon experience with regard to the rates of post-operative complications and the rates of relapse and survival. The results of the 8 surgical specialists who integrate the permanent staff at the institute and who different varying degrees of experience with regard to time spent exercising their specialties were compared. The results obtained did not show a significant difference among the various surgeons, and this uniformity is explained by the fact that all the therapeutic planning was elaborated through consensus of the whole group, and this could have minimized the effect of experience of a surgeon responsible for the operation. The authors emphasize the importance of pre-operative evaluation for good results and propose that it is in the direction of complete mastery of preliminary work in the area that programs for the formation of new specialists should be directed.